The mechanosensitive Piezo1 channel: structural features and molecular bases underlying its ion permeation and mechanotransduction. (19th December 2017) - Wang, Yubo; Xiao, Bailong
Abstract: The evolutionarily conserved Piezo family of proteins, including Piezo1 and Piezo2, encodes the long‐sought‐after mammalian mechanosensitive cation channels that play critical roles in various mechanotransduction processes such as touch, pain, proprioception, vascular development and blood pressure regulation. Mammalian Piezo proteins contain over 2500 amino acids with numerous predicted transmembrane segments, and do not bear sequence homology with any known class of ion channels. Thus, it is imperative, but challenging, to understand how they serve as effective mechanotransducers for converting mechanical force into electrochemical signals. Here, we review the recent major breakthroughs in determining the three‐bladed, propeller‐shaped structure of mouse Piezo1 using the state‐of‐the‐art cryo‐electron microscopy (cryo‐EM) and functionally dissecting out the molecular bases that define its ion permeation and mechanotransduction properties, which provide key insights into clarifying its oligomeric status and pore‐forming region. We also discuss the hypothesis that the complex Piezo proteins can be deduced into discrete mechanotransduction and ion‐conducting pore modules, which coordinate to fulfil their specialized function in mechanical sensing and transduction, ion permeation and selection. Abstract : The cryo‐EM structure and models of mPiezo1. Top panels, extracellular side and intracellular view of the 3D cryo‐EM density map superimposed with a poly‐alanine model and the crystal structure of the trimeric CED. Three protomers are coloured in cyan, purple and green, respectively. Lower panels, illustration of the discrete mechanotransduction and pore modules of the Piezo1 channel in either a structural model (left) or a topology model (right). Adapted from Ge et al . (2015 ) and Zhao et al . (2016 ).